Measurement of subgroups of peripheral blood T lymphocytes in patients with severe acute respiratory syndrome and its clinical significance - 唐小平 尹炽标 张复春 付永贵 陈伟烈 陈燕清 王建 贾卫东 徐安龙 (Chinese medical journal, 2003)
Objective To investigate the changes of subgroups of peripheral blood T lymphocytes in patients with severe acute respiratory syndrome (SARS) and its clinical significance.Methods Subgroups of blood T lymphocytes in 93 patients with SARS were detected by flow cytometer. The results detected in 64 normal subjects and 50 patients with AIDS served as controls.Results The numbers of CD3^ ±, CD4^ ±, and CD^8± lymphocytes all significantly decreased in acute phase of patients with SARS [( 722 ± 533 )/μl, ( 438 ± 353 )/μl, ( 307 ± 217 )/μl) ] compared with those in normal controls [ ( 1527 ± 470 )/μl, (787 ± 257 )/μl, (633 ± 280)/μl, all P < 0.01 ) ], which was different from what we observed in patients with AIDS who had decreased CD4^±[(296 ±298)/μl ]but increased CD8^±[ (818 ± 566)/μl ] counts. The counts of CD3^± , CD4^± , and CD8^±lymphocytes decreased more apparently in patients with severe SARS. All the five patients who died had CD4^±counts less than 200/μl. As the patients' condition improved, CD3^±, CD4^±, and CD8^± counts gradually returned to normal ranges.